UPAYA MENGURANGI NYERI ASAM URAT PADA LANSIA MELALUI OBAT TRADISIONAL INDONESIA: TINJAUAN PUSTAKA - Andini, Vira; Neng Diah Ratnasari; Andri Firmansyah; Teguh Panca Arianto; Ricko Dwi Hariyanto (Jurnal Ilmiah Kesehatan Pernus, 2024)
Introduction: Gout, or gout, is a form of arthritis characterized by deep joint inflammation, often in the big toe, caused by the accumulation of uric acid crystals. Factors that cause high uric acid levels include a diet rich in purines, excessive alcohol consumption, metabolic disorders, and genetic factors. Factors that cause gout include an unhealthy diet, a sedentary lifestyle, and genetic factors. Factors that cause high uric acid levels include a diet rich in purines, excessive alcohol consumption, metabolic disorders, and genetic factors. Objective: To treat gout pain in the elderly with traditional medicine. Methods: The research literature used in this study contains selected articles related to efforts to reduce gout pain experienced by the elderly using conventional Indonesian medicine